Letters - Symons, Arthur. author. aut Link
XX, 289 p.
Keywords: A selection of letters by the symbolist critic and poet, Arthur Symons (1865-1945), including correspondence with such figures as James Joyce, W.B.Yeats, Joseph Conrad, Paul Verlaine, Edmund Gosse, Thomas Hardy and Augustus John to reveal the world of literary London at the turn of the century.